Combined Computational and Experimental Study of Inclusion Complexes of Lupinine and its 1,2,3-triazole Derivative with β-cyclodextr in - Nurmaganbetov, Zh.S.; Fazylov, S.D.; Nurkenov, O.A.; Sarsenbekova, A.Zh.; Pustolaikina, I.A.; Seilkhanov, O.T.; Sviderskiy, A.K.; Minayeva, Ye.V. (Eurasian Chemico-Technological Journal, 2025)
The study presents the results of obtaining clathrate inclusion complexes of the alkaloid lupinine (Lup) and its 1,2,3-triazole derivative (Lup-T) using the oligosaccharide β-cyclodextrin (β-CD). The structural features of the encapsulated forms of lupinine (Lup) and its derivatives were characterized by molecular modeling, IR spectroscopy, 1H and 13C NMR, as well as two-dimensional 1H-1H (COSY) and 1H-13C (HMBC, HSQC) NMR spectroscopy. A comparative thermal degradation study of lupinine, its triazole derivative, and their inclusion complexes with β-cyclodextrin was performed using differential thermogravimetry (DTG) and differential scanning calorimetry (DSC). The kinetic parameters of the thermal decomposition reactions of lupinine-based substrates at different heating rates, along with the values of apparent activation energy, were calculated using modelfree isoconversional methods by Friedman and Ozawa-Flynn-Wall.
Keywords: Lupinine alkaloid; β-cyclodextrin; Quinolizidine derivatives; 1,2,3-triazoles; Inclusion complexes